1977
DOI: 10.1093/infdis/136.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal Colonization with Haemophilus influenzae Type b: A Longitudinal Study of Families with a Child with Meningitis or Epiglottitis Due to H. influenzae Type b

Abstract: A longitudinal study of pharyngeal colonization with Haemophilus influenzae type b included 264 members of families that had a child with meningitis or epiglottitis due to this organism. It was found that (1) 52 of 67 such families contained at least one carrier of H. influenzae type b, who was usually a sibling; (2) H. influenzae type b spread slowly in 39 families colonized continuously during a six-month period, with only eight of 19 uncolonized siblings acquiring the organism during that time; (3) 18 of 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
3
1

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 21 publications
1
26
3
1
Order By: Relevance
“…Only a few of the parents of index patients in our study group were colonized with Hib. The 6% rate for both fathers and mothers differs from rates of 3 and 20%, respectively, reported previously (15). The differences in frequencies of maternal (6 versus 20%) and sibling colonization (45 versus 68%; P < 0.01) observed here and previously may be explained in part by attendance in day-care, which leads to fewer contact hours within a household setting.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Only a few of the parents of index patients in our study group were colonized with Hib. The 6% rate for both fathers and mothers differs from rates of 3 and 20%, respectively, reported previously (15). The differences in frequencies of maternal (6 versus 20%) and sibling colonization (45 versus 68%; P < 0.01) observed here and previously may be explained in part by attendance in day-care, which leads to fewer contact hours within a household setting.…”
Section: Discussioncontrasting
confidence: 60%
“…The rate of pharyngeal colonization with Hib among siblings of index patients within this study was 45%; Michaels and Norden reported a rate of 68% (15). Only a few of the parents of index patients in our study group were colonized with Hib.…”
Section: Discussioncontrasting
confidence: 45%
“…44 What accounts for the stronger and more enduring anti-PRP responses in infants in developing countries and do the persisting high titers protect against disease? The enhanced anti-PRP responses in developing country infants could derive from immunologic priming consequent to more extensive colonization with Hib 45,46 or with other bacteria expressing polysaccharides that cross-react with PRP (e.g., E. coli expressing K100) 4,[47][48][49][50] ; such immunologic priming may occur even though the infant does not exhibit serum anti-PRP antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent colonization, however, is associated with development of natural immunity [64,65] and is likely the cause of the natural decline in incidence of invasive disease with age amongst unvaccinated children [66].…”
Section: Mechanism Of Vaccine Protectionmentioning
confidence: 99%